PERLINDUNGAN KEPEMILIKAN TANAH DARI GUGATAN PEMILIK SERTIFIKAT TERLAMA ATAS DASAR JUAL BELI TANAH YANG BERSERTIFIKAT STUDI PUTUSAN PENGADILAN NO : 30/PDT.G/2009/PN.KBJ - FERANITA BARUS (PREMISE LAW JURNAL, 2016)
Buy and sell is an agreement in which the first party (seller) binds himself to give (ownership upon) something to the other party (buyer) to pay a promised price which is in line with Article 1457 of the Civil Code. Often in land transactions where an issue arises after the sale and purchase of land between the Seller and the Buyer, the other party that the certificate owner longest objected to the occurrence of the land transactions. This proves there has been a dispute over double the certificate. The research used descriptive analytic. The results showed that the claim from the owner of the oldest certificate for the certified land purchase occurred because the lay and the borders of the land in the certificate owned by the oldest certificate holder are not obviously stated: also, he never occupied or took care of the lan. As to the legal certainty of certificate of title, it is valid as long as there is no claim/objection from other party who has evidence as the owner who has stronger entitlement on the land concerning the defense on the land rights. Keywords : Defense, Land Purchase, The Owner of the Oldest Certificate